2018
DOI: 10.3892/ol.2018.9432
|View full text |Cite
|
Sign up to set email alerts
|

Barrier‑to‑autointegration factor 1: A novel biomarker for gastric cancer

Abstract: China is a country with a high incidence of gastric cancer (GC), where the GC incidence and the resultant mortality rates account for 50% of those worldwide. Surgical resection remains the primary treatment for GC. However, postoperative patients have a poor prognosis as the majority of patients present with metastases at the time of diagnosis. Therefore, the identification of novel treatment targets is required. The present study aimed to determine the effects of barrier-to-autointegration factor 1 (BANF1) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…These results revealed the essential role of BANF1 in regulating the mitotic process and normal cell cycle progression. Moreover, BANF1 has been reported to be a novel biomarker for gastric cancer ( 30 ). In one of our previous studies, it was shown that BANF1 was highly expressed in ESCC and that its expression was associated with the TNM stage and the tumor differentiation degree of ESCC patients ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results revealed the essential role of BANF1 in regulating the mitotic process and normal cell cycle progression. Moreover, BANF1 has been reported to be a novel biomarker for gastric cancer ( 30 ). In one of our previous studies, it was shown that BANF1 was highly expressed in ESCC and that its expression was associated with the TNM stage and the tumor differentiation degree of ESCC patients ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…11 In addition, Li reported that BANF1 expression is increased in gastric cancer and associated with the poor prognosis of patients, which was a novel biomarker for gastric cancer. 12 Our experimental results showed that the expression of BANF1 was significantly increased in TNBC tissues, indicating that BANF1 plays an important role in the carcinogenesis of TNBC. BANF1 protein was not only highly expressed in TNBC, but also related to the clinicalpathological parameter, such as the status of lymph node metastasis and TNM stage, which indicated that the progression of TNBC may be related to the expression of BANf1.…”
Section: Discussionmentioning
confidence: 58%
“…Importantly, we confirmed the colocalization of p16 with a protein subset previously involved in carcinogenesis with a specific role in nuclear shuttling. For instance, BANF1 has been reported to be involved in colony formation, migration and invasion in CC [37] and in the development of hepatocellular [23] and esophageal squamous cell [24] carcinomas and gastric cancer [26]. It is also known to interact with a protein which prevents nuclear accumulation of other proteins, such as β-catenin [38].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the cytoplasmic p16 interactors identified by LC-MS/MS were selected for further examination by double immunofluorescence because of their involvement in other carcinogenic processes [23][24][25][26][27][28][29]. As seen in Figure 4C, we found that CDK4, the A-kinase anchor protein 8 (AKAP8), the barrier to autointegration factor (BANF1), and the type-1 angiotensin II receptor-associated protein (AGTRAP) colocalized with p16 in the cytoplasm of SiHa cells, confirming that these proteins interact with cytoplasmic p16 in SiHa cells.…”
Section: Colocalization Of Cytoplasmic P16 and Interactors In Siha Cellsmentioning
confidence: 99%